Prescription of oxygen concentrators and survival in Northern Ireland. - Heaney, L. G. (Ulster Medical Society, 1997)
Long-term oxygen therapy (LTOT) has been shown to prolong survival and to improve quality of life in patients with chronic obstructive pulmonary disease (COPD) and in respiratory failure. In Northern Ireland oxygen concentrators have been available on prescription since August 1986, initially on a restricted basis from hospital physicians only. This was followed by open prescribing from April 1989, when concentrators could be prescribed by general practitioners. This study examined prescribing habits of LTOT during both periods, and patient survival. Case notes of all prescriptions of oxygen concentrators in Northern Ireland (to April 1991) were reviewed. Prescription criteria and advice regarding usage during both periods were analysed. A questionnaire survey of subjects during open prescribing documented the advice given at the time of prescription and current usage. 164 charts of 178 total installations were available for review. During both periods many concentrators were installed without adherence to the prescribing criteria at the time (75% restricted, 48% open). The majority of these were on the advice of a consultant respiratory physician and only 14 were prescribed directly by GPs. 89 of 91 subjects receiving current LTOT during the study period completed questionnaires. Of the subjects prescribed LTOT during the restricted period, 2 subjects are still alive (median survival 19 m, range 0-104). From the open period, survival data was available on 107 of 129 subjects with 17 still alive (median survival 22 m, range 0-94). This study documents an inadequate rate of prescribing and a lack of conformity to guidelines in the provision of LTOT in Northern Ireland. We would suggest that familiarisation with the prescribing criteria, formal written advice at the time of prescription, appropriate follow up to ensure adequate supplementation and regular patient education on the use of LTOT would address these problems to a substantial degree.